Before it's too late: The extinction script, multi‐species reproductive futurism and Extinction Rebellion - Robson, Amy (Transactions - Institute of British Geographers (1965), 2025)
Whether it's a speech from a politician, a warning in a scientific article, or activists chanting in the street, the climate crisis is made and remade through competing claims about the future. Across Western environmental movements, such claims often take the form of calls to forestall looming planetary extinction. The belief that we have to act now to avoid a future lost knowingly to self‐inflicted extinction operates through what I term ‘the extinction script’. As a technology of power that regulates climate futures, the extinction script implores the already threatened subject to act now and to do so urgently. Developing Edelman's (2004) concept of reproductive futurism, this paper argues that the extinction script enacts a dominant mode of relation to the future—that of ‘multi‐species reproductive futurism’. To do so, this paper traces and analyses the presence of the extinction script across public performances of activism by focusing upon the environmental movement Extinction Rebellion UK. Drawing from ethnographic fieldwork that spanned across 18 months, this paper offers a novel approach for understanding how individuals imagine collective futures. Short The belief that we have to act now to avoid a future lost knowingly to self‐inflicted extinction operates through what I term ‘the extinction script’. As a technology of power that regulates climate futures, the extinction script implores the already threatened subject to act now and to do so urgently. This paper traces and analyses the presence of the extinction script across public performances of activism by focusing upon the environmental movement Extinction Rebellion UK.